2014
DOI: 10.1016/j.jgr.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of physicochemical and NMR data of triol ginsenosides Re, Rf, Rg2, and 20-gluco-Rf from Panax ginseng roots

Abstract: Ginseng roots were extracted with aqueous methanol, and extracts were suspended in water and extracted successively with ethyl acetate and n-butanol. Column chromatography using the n-butanol fraction yielded four purified triol ginseng saponins: the ginsenosides Re, Rf, Rg2, and 20-gluco-Rf. The physicochemical, spectroscopic, and chromatographic characteristics of the ginsenosides were measured and compared with reports from the literature. For spectroscopic analysis, two-dimensional nuclear magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…The 13 C-NMR (Table 2) spectrum showed 51 carbon signals, including a pair of olefinic carbons at C-24 ( δ c 126.501) and C-25 ( δ c 131.495), two oxygen-substituted carbons at C-6 ( δ c 75.122) and C-20 ( δ c 83.925), and two carbonyl-group signals at C-M1 ( δ c 169.308) and C-M3 ( δ c 171.075). These data suggest that compound 1 was a dammarane-type triterpene glycoside with a double bond and a malonyl group [15], [16], [17], [18]. The chemical structure of compound 1 was further elucidated by a HMBC (Figure 2) experiment in which correlations were observed between H-1′ ( δ H 5.22, d, J  = 6.8 Hz ) and the carbon resonance signal at C-6 ( δ c 75.122 ), H-1′′ ( δ H 6.46, brs ) and C-2′ ( δ c 79.083 ), and H-1‴ ( δ H 5.04, d, J = 7.7 Hz ) and C-20 ( δ c 83.925 ), which indicated that the C-1 Glc′ , C-1 Glc′′ , and C-1 Rha′′′ were linked to C-6, C-2′, and C-20, respectively.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The 13 C-NMR (Table 2) spectrum showed 51 carbon signals, including a pair of olefinic carbons at C-24 ( δ c 126.501) and C-25 ( δ c 131.495), two oxygen-substituted carbons at C-6 ( δ c 75.122) and C-20 ( δ c 83.925), and two carbonyl-group signals at C-M1 ( δ c 169.308) and C-M3 ( δ c 171.075). These data suggest that compound 1 was a dammarane-type triterpene glycoside with a double bond and a malonyl group [15], [16], [17], [18]. The chemical structure of compound 1 was further elucidated by a HMBC (Figure 2) experiment in which correlations were observed between H-1′ ( δ H 5.22, d, J  = 6.8 Hz ) and the carbon resonance signal at C-6 ( δ c 75.122 ), H-1′′ ( δ H 6.46, brs ) and C-2′ ( δ c 79.083 ), and H-1‴ ( δ H 5.04, d, J = 7.7 Hz ) and C-20 ( δ c 83.925 ), which indicated that the C-1 Glc′ , C-1 Glc′′ , and C-1 Rha′′′ were linked to C-6, C-2′, and C-20, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…Other carbon shifts included an upfield shift of C-5‴ ( δ C 75.389) and a downfield shift of C-6‴ ( δ C 65.755), as compared to ginsenoside Re [15], [16]. H-5‴ yielded a peak at 3.96, and H-6‴ at 4.98 and 4.71, based on the HSQC spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Sun reported the total saponin content in ginseng root hair as being higher than that in other parts of ginseng. Ginseng has drawn attention as a traditional medicine worldwide because of its various functions, such as anti‐diabetes, anti‐inflammatory, antioxidant and anticancer activities …”
Section: Introductionmentioning
confidence: 99%
“…Ginseng has drawn attention as a traditional medicine worldwide because of its various functions, such as anti-diabetes, anti-inflammatory, antioxidant and anticancer activities. [5][6][7][8][9][10][11][12][13] Baek et al 14 reported that heat processing led to chemical and structural changes, improving the biological activities. Extrusion has been considered as a high-temperature short-time process to produce commercial products for over 50 years, because of its high productivity, energy efficiency and versatility.…”
Section: Introductionmentioning
confidence: 99%
“…Glc = glucose; Ara(p) = alpha-l arabinopyranose, Ara(f) = alpha-L arabinofuranose, Rha = rhamnose. (C) Summary of previous reports[15][16][17] on the 1 H NMR assignments of major ginsenosides. The highlighted ginsenosides are assigned inFig.…”
mentioning
confidence: 99%